Moderating online child sexual abuse material (CSAM): Does self-regulation work, or is greater state regulation needed? - Bleakley, Paul (European journal of criminology, 2024)
Social media platforms are crucial public forums connecting users around the world through a decentralised cyberspace. These platforms host high volumes of content and, as such, employ content moderators (CMs) to safeguard users against harmful content like child sexual abuse material (CSAM). These roles are critical in the social media landscape however, CMs? work as ?digital first responders? is complicated by legal and systemic debates over whether the policing of cyberspace should be left to the self-regulation of technology companies, or if greater state-regulation is required. In this empirical policy and literature review, major debates in the area of content moderation and, in particular, the online policing of CSAM are identified and evaluated. This includes the issue of territorial jurisdiction, and how it obstructs traditional policing; concerns over free speech and privacy if CMs are given greater powers, and debates over whether technology companies should be legally liable for user-generated content (UGC). In outlining these issues, a more comprehensive foundation for evaluating current practices for monitoring and combatting online CSAM is established which illustrates both the practical and philosophical challenges of the existing status quo, wherein the state and private companies share these important responsibilities.